Health-Related Quality of Life in Patients with Chronic Kidney Disease in Hemodialysis in Medellín (Colombia) (2019)
ABSTRACT : Purpose: Hemodialysis is a treatment that is essential for the survival of patients with terminal chronic kidney disease. However, it is highly invasive, non-curative, and physically, psychologically, socially, and financially demanding, which has an impact on the patient’s health-related quality of life (HRQL). In Colombia, research from the point of view of patients undergoing hemodialysis is scarce. Patients and methods: We conducted a cross-sectional study involving 142 patients undergoing hemodialysis. We used an instrument that included the demographic and clinical information as well as the Charlson Comorbidity Index and Karnofsky Performance Status Scale. HRQL was assessed using EQ-5D-5L and KDQOL-36. The analysis was done using measures of central tendency for quantitative variables and relative frequencies for qualitative variables, in addition bivariate and multivariate regression analyses were conducted. Results: Based on the scores of the EQ-5D-5L scale, it was found that 14.5% subjects showed severe mobility problems, 5.8% were unable to bathe or dress by themselves, 12.9% were unable to perform usual activities, 13.5% were experiencing pain or discomfort (between strong and extreme), and 58.6% showed a certain degree of anxiety or depression. The KDQOL-36 scores were 67.4 ± 19.4 for the symptoms domain and 35.0 ± 27.5 for the disease burden domain. Results of the linear regression analysis showed that the main factors associated with HRQL were the Karnofsky Index and serum albumin levels (p < 0.05). Conclusion: The result of this study revealed the impact on the quality of life of Colombian patients undergoing hemodialysis with chronic kidney disease who were highly affected by the disease burden. KDQOL-36 has excellent properties of reliability, internal consistency, and discriminant power; thus, its use is recommended in subsequent studies to monitor HRQL in this population.